PENGARUH HARGA, SOSIAL MEDIA MARKETING DAN BRAND EQUITY TERHADAP CUSTOMER PURCHASE DECISION MELALUI CONSUMER RESPON SEBAGAI VARIABEL INTERVENING PADA JAMAAH UMROH PT SARAYA ANUGRAH DI SIDOARJO - Masruroh, Dwi Mariana; Sardjono, Sigit; Halik, Abdul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
The use of e-commerce in Indonesia is currently experiencing very rapid development.Social media is considered successful in giving a way of communicating and interacting with internet users within a limited period of time The purpose of this research are to analyze the influence of social media marketing and brand equity towards customer purchase decision through consumer response as a variable intervening oh umrohpilgrims PT Saraya Anugrah in Sidoarjo. This research uses analytical method with two methods in the analysis process namely first covariance based structural equation modeling method (CBSEM). Target population in this research is umroh pilgrims that amounting to 150 respondent. Resultf of this research are 1. price perception has a positive effect and significant to consumer responses 2. price perception has a positive effect and significant to customer purchase decision 3. social media marketing has a positive effect and significant to customer responses 4. social media marketing has not positive effect and significant to customer purchase decision 5. brand equity has a positive effect and significant to customer responses 6. brand equity has not positive effect and significant to customer purchase decision 7. consumer responss has a positive effect and significant to customer purchase decision